Rhetorical Patterns in the Writing of Introduction Section of Research Articles in English Academics - Ramadhanty, Nadya; Sutrisno, Adi (e-Journal of Linguistics; Vol 16 No 1 (2022): ejl-JanuaryDO - 10.24843/e-jl.2022.v16.i01.p13, 2021)
This research is aimed at investigating the Rhetorical Structures used by the authors in the introduction section of research articles published by two different journals, namely Journal of Pragmatics and Journal of English for Academic Purposes. This research examined whether introduction section of the selected research articles follow the essential moves and steps according to CARS model by Swales (2004). In so doing, ten introduction sections in the research articles were selected in this research. The articles were purposively chosen in the amount of five research articles from each of the journals. The result showed the introduction sections in both   journals employed most of the moves and steps of CARS model proposed by Swales (2004).